Solvent-templated methylammonium-based Ruddlesden–Popper perovskites with short interlayer distances - Zhumekenov, Ayan A. (2024)
Two-dimensional (2D) halide perovskites are exquisite semiconductors with great structural tunability. They can incorporate a rich variety of organic species that not only template their layered structures but also add new functionalities to their optoelectronic characteristics. Here, we present a series of new methylammonium (CH3NH3+ or MA)-based 2D Ruddlesden-Popper perovskites templated by dimethyl carbonate (CH3OCOOCH3 or DMC) solvent molecules. We report the synthesis, detailed structural analysis, and characterization of four new compounds: MA2(DMC)PbI4 (n=1), MA3(DMC)Pb2I7 (n=2), MA4(DMC)Pb3I10 (n=3), and MA3(DMC)Pb2Br7 (n=2). Notably, these compounds represent unique structures with MA as the sole organic cation both within and between the perovskite sheets, while DMC molecules occupy a tight space between the MA cations in the interlayer. They form hydrogen-bonded [MA⋯DMC⋯MA]2+ complexes that act as spacers preventing the perovskite sheets from condensing into each other. We report one of the shortest interlayer distances (~5.7–5.9 Å) in solvent-incorporated 2D halide perovskites. Furthermore, the synthesized crystals exhibit similar optical characteristics to other 2D perovskite systems, including narrow photoluminescence (PL) signals. The density functional theory (DFT) calculations confirm their direct-bandgap nature. Meanwhile, the phase stability of these systems was found to correlate with the H-bond distances and their strengths, decreasing in the order: MA3(DMC)Pb2I7 > MA4(DMC)Pb3I10 > MA2(DMC)PbI4 ~ MA3(DMC)Pb2Br7. The relatively loosely bound nature of DMC molecules enables us to design a thermochromic cell that can withstand 25 cycles of switching between two colored states. This work exemplifies the unconventional role of the non-charged solvent molecule in templating the 2D perovskite structure.